Overuse of Intravenous Proton Pump Inhibitors in General Medicine and Surgery Wards - Shah, Jay N; Shah, Jenifei; Sharma, Pawan; Shah, Jesifei; Pandey, Ashim; Joshi, Chunauti; Adhikari, Devesh; Gurung, Grisha; Khatri, Kalpashri; Basnet, Lisa; Shah, Shailendra; Dahal, Romi; et al. (Journal of Nepal Health Research Council, 2023)
Background: Overuse of stress ulcer prophylaxis is prevalent globally despite guidelines leading to the added cost, especially the intravenous proton pump inhibitor (IVPPI). This study aims to analyze the prevalence of such overuse and be aware of rational use which may help develop local guidelines. Methods: This study analyzed the prospectively collected data on IVPPI use in adult patients in general wards of medicine and surgery at Patan Hospital, Patan Academy of Health Sciences, Nepal, from April-Jun 2022. Ethical approval was obtained. Variables analyzed were the patient’s age, gender, history of peptic ulcer disease, risk for stress ulcer and gastrointestinal bleeding, the status of nil per os (NPO ?12 hours), appropriate use of IVPPI, and cost. Results: Prevalence of IVPPI use was 36.24% (274/756 admissions), surgery 39.45(189/479), medicine ward 30.68% (85/277). The mean age was 43.1 ±18.6 years, males 113(41.2%), surgery 189 (69%). Inappropriate overuse in 253(92.3%, significantly more in surgery-182 than medicine-7, p=0.001. Appropriate use was in 21 (7.7%, i.e., NPO-15, NPO + gastrointestinal bleed, and NPO + non steroid anti-inflammatory drugs each 3). Conclusions: Prevalence of IVPPI use was 36.24%. Inappropriate overuse of IVPPI was high (92.2%, 253/274), more in surgery. The nil per os status was the main reason for appropriate use of IVPPI. Keywords: Acid suppression therapy; cost; general medical surgical ward; intravenous proton pump inhibitor; stress ulcer prophylaxis guideline.